2018
DOI: 10.3758/s13415-018-0611-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity of reflective and brooding rumination in depressed and healthy women

Abstract: Ruminative thinking is related to an increased risk for major depressive disorder (MDD) and perpetuates negative mood states. Rumination, uncontrollable negative thoughts about the self, may comprise both reflective and brooding components. However, only brooding rumination is consistently associated with increased negativity bias and negative coping styles, while reflective rumination has a less clear relationship with negative outcomes in healthy and depressed participants. The current study examined seed-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 128 publications
(159 reference statements)
7
27
0
Order By: Relevance
“…Alterations in FC associated with rumination have also been indicated for MPFC seed connectivity. Increased resting-state FC between the MPFC seed and the PCC was correlated with reflective rumination for female participants with major depressive disorder (MDD) (Satyshur et al, 2018). This result is partly consistent with the present result that found the association between reflective RRS and the MPFC connectivity (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Alterations in FC associated with rumination have also been indicated for MPFC seed connectivity. Increased resting-state FC between the MPFC seed and the PCC was correlated with reflective rumination for female participants with major depressive disorder (MDD) (Satyshur et al, 2018). This result is partly consistent with the present result that found the association between reflective RRS and the MPFC connectivity (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…While depressive and brooding components, rather than reflective component of RRS have been associated with the pathological effect of rumination (Watkins and Teasdale, 2004), the current data indicated that MA participants had significantly high reflective RRS as well as depressive and brooding RRS. High RRS in both reflective and brooding components was also observed in another study (Satyshur et al, 2018). This observation was consistent with the study indicating that brooding and reflective rumination were not separate factors in depressed patients because these components could exacerbate each other in depression (Whitmer and Gotlib, 2011).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, one possibility is that the RSC is involved in attentional shifting in rodents as a function of its striatal territory. As a hub of the DMN, RSC in humans is known to be impaired in various psychiatric and neurological disorders (Doucet et al, 2020;He et al, 2018;Satyshur, Layden, Gowins, Buchanan, & Gollan, 2018;Martino et al, 2016;Wu et al, 2016;Baker et al, 2014;Cowdrey, Filippini, Park, Smith, & McCabe, 2014;Hafkemeijer, van der Grond, & Rombouts, 2012;Anderson et al, 2011;Bluhm et al, 2009). Understanding the biology of the DMN will require a detailed, translational explication of the functional roles of the RSC, not just in navigation and memory, but also in decision making.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, brooding and reflective rumination are associated with different functional connectivity patterns in healthy and depressed women at rest (Satyshur, Layden, Gowins, Buchanan, & Gollan, 2018). Brooding rumination has been associated with increased connectivity between the posterior and subgenual cingulate cortex at rest, before and after controlling for depressive symptoms (Berman et al, 2011) as well as decreased functional connectivity between the left amygdala and right temporal pole (Satyshur et al, 2018). This pattern of connectivity further illustrates the role brooding rumination may play in enhanced amygdala activation leading to enhanced memory modulation following stressor exposure.…”
Section: Potential Mechanismsmentioning
confidence: 99%